2021
DOI: 10.3390/cells10123577
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dose- and Tissue-Dependent Effects of foxo on Aging, Metabolic and Proteostatic Pathways

Abstract: Aging is the gradual deterioration of physiological functions that culminates in death. Several studies across a wide range of model organisms have revealed the involvement of FOXO (forkhead box, class O) transcription factors in orchestrating metabolic homeostasis, as well as in regulating longevity. To study possible dose- or tissue-dependent effects of sustained foxo overexpression, we utilized two different Drosophila transgenic lines expressing high and relatively low foxo levels and overexpressed foxo, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Since advanced glycation end products accumulate during aging and age-associated diseases, a recent study demonstrated, by using quantitative proteomics, that protein glycation triggers a proteotoxic response and indirectly affects the protein degradation machinery regulating the cellular function compromised during aging [107]. An interesting article demonstrated that FOXO (forkhead box, class O) transcription factors regulate metabolic homeostasis as well as longevity using Drosophila transgenic lines expressing high and relatively low foxo levels and overexpressed foxo, either ubiquitously or in a tissue-specific manner [108]. Ubiquitous foxo overexpression accelerates aging inducing the early onset of age-related phenotypes, increasing the sensitivity to thermal stress, and deregulating metabolic and proteostatic pathways.…”
Section: Proteostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Since advanced glycation end products accumulate during aging and age-associated diseases, a recent study demonstrated, by using quantitative proteomics, that protein glycation triggers a proteotoxic response and indirectly affects the protein degradation machinery regulating the cellular function compromised during aging [107]. An interesting article demonstrated that FOXO (forkhead box, class O) transcription factors regulate metabolic homeostasis as well as longevity using Drosophila transgenic lines expressing high and relatively low foxo levels and overexpressed foxo, either ubiquitously or in a tissue-specific manner [108]. Ubiquitous foxo overexpression accelerates aging inducing the early onset of age-related phenotypes, increasing the sensitivity to thermal stress, and deregulating metabolic and proteostatic pathways.…”
Section: Proteostasismentioning
confidence: 99%
“…Ubiquitous foxo overexpression accelerates aging inducing the early onset of age-related phenotypes, increasing the sensitivity to thermal stress, and deregulating metabolic and proteostatic pathways. In particular, foxo overexpression counteracts the proteostatic pathways in an Nrf2/cncC dependent-manner, ameliorating the aberrant foxo overexpression-mediated toxicity [108].…”
Section: Proteostasismentioning
confidence: 99%
“…For measuring proteasome peptidase activity, 10 dissected flies' tissues (equal number of males and females) were lysed on ice in a buffer suitable for isolation of intact 26S proteasomes (0.2% NP-40, 5 mM ATP (fresh), 10% glycerol, 20 mM KCl, 1 mM EDTA, 1 mM DDT, and 20 mM Tris, pH 7.6). Protein content was adjusted with Bradford (Bio-Rad, Hercules CA, USA) and cleared supernatants were immediately used to determine the chymotrypsin-like (CT-L/LLVY) or caspase-like (C-L/LLE) proteasome proteolytic activities after recording (excitation, 350 nm; emission, 440 nm) the hydrolysis of the fluorogenic peptides Suc-Leu-Leu-Val-Tyr-AMC and Z-Leu-Leu-Glu-AMC, (Enzo Life Sciences, Farmingdale, NY, USA), respectively, at 37 • C for 30 min [24,25]. Equal numbers of male and female flies were used.…”
Section: Preparation Of Tissue Protein Extracts Immunoblot Analysis M...mentioning
confidence: 99%
“…Furthermore, FOXO proteins promote numerous downstream target genes encoding antioxidant enzymes that regulate redox homeostasis, including superoxide dismutase Oxidative Medicine and Cellular Longevity (SOD) and catalase, in an NAD + -dependent manner [170]. In addition, genetic variants of FOXO3 are associated with longevity in worms, flies, and mammals, and protective alleles of FOXO3 are the second most replicated genetic factors related to prolonged human life, with findings of about 40 unique nucleotide polymorphisms (SNPs) noncoding consistently associated with longevity in humans [171].…”
Section: The Antioxidant Systemmentioning
confidence: 99%